The quality of inter‑organizational relations and the intention of commercialization of knowledge by academic entrepreneurs – a theoretical approach and outline of research - Kobylińska, Urszula (Contemporary organisation and management. Challenges and trends, 2020)
The main purpose of this article is to develop a framework to study the impact of high-quality inter-organizational relationships (between scientists and supporting institutions) on academic entrepreneurs’ willingness to commercialize research results. The concept of the theoretical model was developed on the basis of a literature review and available empirical research results. The specific objectives of the article include the identification of key institutions supporting academic entrepreneurs, and the identification of factors building the quality of inter-organizational relations. The developed model is only a preliminary and partial proposal to measure the intent of commercializing research results by academic entrepreneurs, taking into account one of the important aspects of this process, namely the quality of relationships.